IMPLEMENTASI MODEL SCRUM PADA SISTEM INFORMASI PEMBELAJARAN DILUAR KAMPUS UNTUK SKEMA WIRAUSAHA KAMPUS MERDEKA (STUDI KASUS: UNIVERSITAS CATUR INSAN CENDEKIA) - Putri Agriza Nur Azizah; Marsani Asfi; Ilwan Syafrinal (Universitas Singaperbangsa Karawang, 2021)
Information technology is very important for students who want todevelop their business in the modern business world. Preparation formand the system product that can be done is an information systemstudent entrepreneurs using online payment methodswhich can be used as facilities and services to supportIndependent Campus Entrepreneurship Program for Catur University studentsScholar Man. The design of this system uses the SCRUM methodwhich is very suitable to be applied because of the speed in the processinteractive, multi-demand information system developmentincremental, thus requiring developers to use methodsdevelopment that allows change at any time. Scrum Phaseincludes Product Backlog, Sprint Planning, Sprint Backlog, Sprint, SprintReview, and Retrospective. Scrum roles include Product Owner, ScrumMasters, and Development Team. The results of this study ImplementationSCRUM Model on Entrepreneurial Information Systems to supportimplementation of the independent campus program at the Catur Insan UniversityCirebon scholars by using an online payment system thatintegrated with Ipaymu and successfully completed within 4Sprint in SCRUM. This system is web-based using the languagePHP programming and CodeIgnite Framework.